Affixation In Arabic-Indonesian And Its Effect On Change Of Meaning/ أحرف الزيادة في اللغة العربية واللغة الإندونيسية وتأثيرها في تغيير المعنى - Ahmad Abdul Rahman; Asikin Nor; Sajidah Sajidah; Faisal Mubarak; M. Kamil Ramma Oensyar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
One of the branches of morphology is affixation. Affixation is a bound morpheme that is placed on the base morpheme. This article aims to describe: 1) the similarities in affixation in Arabic and Indonesian, 2) the differences in affixation in Arabic and Indonesian, and 3) the effect of affixation on the change of meaning. This research is a literature study using a qualitative approach with a contrastive analysis method, namely comparing by looking for similarities and differences between the two languages (Arabic and Indonesian) and also using constant analysis. The primary data in this study is the Qur'an, namely Surah Al-Mu'minun, and its translation, and secondary data are taken from books related to the research. The results showed similarities between Arabic and Indonesian affixation in Surah Al-Mu’minūn, namely the affixation with prefixes and suffixes, and there were two additional affixations in one word. The difference is that in Arabic, only affixation, while in Indonesian, affixation and pronouns. And the effects of the change of meaning in Arabic are in the form of gender (masculine and feminine) and the structure of numbers (singular, dual, and plural). In Indonesian, noun and adjective forms change to verbs. And for both (Arabic and Indonesian) change in active and passive forms of verbs and change in command words.